Who is Paying for the Trade War with China? - Benedikt Zoller-Rydzek; Gabriel Felbermayr (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
On September 24th 2018, the United States introduced import tariffs on a wide range of Chinese products. The tariffs will affect US imports from China with a value that exceeds USD 250 billion -around 50% of all imports. In this analysis we show that, contrary to public opinion, the greatest share of the tariff burden falls not on American consumers or firms, but on Chinese exporters. We calibrate a simple economic model and find that a 25 percentage point increase in tariffs raises US consumer prices on all affected Chinese products by only 4.5% on average, while the producer price of Chinese firms declines by 20.5%. The US government has strategically levied import duties on goods with high import elasticities, which transfers a great share of the tariff burden on to Chinese exporters. Chinese firms pay approximately 75% of the tariff burden and the tariffs decrease Chinese exports of affected goods to the United States by around 37%. This implies that the bilateral trade deficit between the US and China drops by 17%. The additional tariffs generate revenues of around USD 22.5 billion, which could subsequently be redistributed in the US. Although the tariffs introduce a distortion to US consumption decisions, the economic costs are shifted to Chinese exporting firms and the US government is able to extract a net welfare gain of USD 18.4 billion. Autor, Dorn and Hanson (2013, 2016) show that Chinese import competition can have dramatic negative effects on the US labour market. On the other hand, most economists agree that international trade has positive effects for the economy as a whole. The overall gains from trade are high enough to compensate those groups that lose out. These opposing views also characterise general public opinion in the US. Stokes (2018) shows that most Americans believe that international trade is good for the economy, but that they personally do not gain from it, particularly in the labour market. Trade in general, and the US trade deficit with China in particular, has a bad reputation.
Keywords: 330